PEMBELAJARAN APRESIASI DONGENG - Yunida Fitratun Nisa; Nurlaksana Eko Rusminto; Siti Samhati (Jurnal Kata (Bahasa, Sastra, dan Pembelajarannya), 2013)
Learning of the fairy tale’s appreciation in class VII A at SMP Negeri 1 was the problem of this research study. The learning activities were seen based on the planning of the learning, the implementation of the learning, and the evaluation of the learning. The method used in this study was descriptive qualitative. The subject of this research was the learning activities between the teacher of Indonesian lesson and the students. The research result showed that the learning of fairy tale’s appreciation in class VII A consisted of the lesson plan made by the teacher, the process of the learning implementation teacher’s activities in teaching and students’, and evaluation. The lesson plan that was made used question and answer method, discussion, and demonstration. The teacher used the media and movie. The implementation of the learning involved the activity of teacher and students. Teacher’s activity was done sequently started from pre-learning, the learning activity, and closing. The students activities run well as the criteria og students activity in learning fairy tale’s appreciation. The students activity involved the activities of speaking, listening, writing, emotion, and mental. The learning evaluation used portofolio and written assessmentKeywords: learning, tale’s appreciation, students of VII A